Halal Industry Development Strategy in The Cosmetics Sector: A Study of Islamic Business Ethics - Sapsuha, Mubasysyyratul Ummah; Siradjuddin, Siradjuddin; Lutfi, Mukhtar (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The development of the halal cosmetics industry is no longer just an option, but an urgent need in the face of changing consumer preferences and global market dynamics. The increasing awareness of the Muslim community towards halal cosmetic products is reflected in the significant growth of the global halal cosmetics market in recent years. This encourages various cosmetic manufacturers to develop their halal product lines, but there are still challenges in implementing halal standards. Using literature studies, this study examines the halal cosmetics industry's development strategy from the Islamic business ethics perspective. This study found that the application of Islamic business ethics in the halal cosmetics industry not only includes the halal aspect of the product but also includes the aspect of consumer safety. For this reason, Islamic business ethics is needed as a strategy for the development of halal cosmetics, namely through the fulfillment of business ethics principles and the implementation of business ethics. The implementation of this strategy (Islamic business ethics) not only creates a competitive advantage for cosmetic manufacturers but also provides a guarantee of halal and product safety for Muslim consumers. In addition, a consumer needs to understand halal and safe cosmetics by checking halal labels and cosmetic composition. So, consumers will not be deceived by cosmetics with fake halal labels or harmful cosmetics.